Analysis of Air Distribution and Comfort in Large Space Environment Simulator. Issue 1 (April 2021) - Wenjing, Ding; Jinghao, Xu; Songlin, Hu; Liming, Zhang; Ang, Li
Abstract: The objective of this paper is to analyze the air distribution and comfort in large space environment simulator under different air supply for the same boundary and initial conditions. This is done by conducting the numerical simulations and contrasting the distribution of velocity and temperature field, PMV-PPD and air age. It can be analyzed that the influence of several air supply on air quality and thermal comfort inside the equipment, which can be as a reference for the improvement and optimization of airflow distribution with the device. This device owns three openable doors, which locate in the bottom, middle and top of the equipment. Open one of them, the ventilation will be achieved. Computational Fluid Dynamics (CFD) is used for it is easier and less time consuming to accomplish that purpose. In general, different air supply have important effect on the air distribution and comfort inside the device. Meanwhile, the comfort is acceptable in most area, however, the air age is on the high side.